You are on page 1of 4

ON THE INFERIOR AND SUPERIOR k-TH POWER PART

OF A POSITIVE INTEGER AND DIVISOR FUNCTION

ZHENG JIANFENG
Shaanxi Financial & Economics Professional College,
Xianyang, Shaanxi, P.R.China

ABSTRACT: For any positive integer n, let a(n) and b(n) denote the inferior and superior k-th power
part of n respectively. That is, a(n) denotes the largest k-th power less than or equal to n, and b(n)
denotes the smallest k-th power greater than or equal to n. In this paper, we study the properties of
the sequences {a(n)} and {b(n)}, and give two interesting asymptotic formulas.

Key words and phrases: Inferior and superior k-th power part; Mean value; Asymptotic formula.

1. INTRODUCTION
For a fixed positive integer k>1, and any positive integer n, let a(n) and b(n) denote the inferior
and superior k-th power part of n respectively .That is, a(n) denotes the largest k-th power less than
or equal to n, b(n) denotes the smallest k-th power greater than or equal to n. For example, let k=2
then a(1)=a(2)=a(3)=1,a(4)=a(5)=…=a(7)=4, …,b(1)=1, b(2)=b(3)=b(4)=4, b(5)=b(6)= …
=b(8)=8…; let k=3 then a(1)=a(2)= …=a(7)=1, a(8)=a(9)= …=a(26)=8,…,b(1)=1, b(2)=b(3)= …
=b(8)=8, b(9)=b(10)=…=b(27)=27…. In problem 40 and 41 of [1], Professor F . Smarandache asks
us to study the properties of the sequences {a(n)} and {b(n)}. About these problems, Professor
Zhang Wenpeng [4] gave two interesting asymptotic formulas of the cure part of a positive integer.
In this paper, we give asymptotic formulas of the k-th power part of a positive integer. That is, we
shall prove the following:
Theorem 1. For any real number x>1 , we have the asymptotic formula
1
1 6 1− + ε
∑ d (a(n)) = kk! ( 2 ) k −1 A0 x ln k x + A1x ln k −1 x +  + Ak −1x ln x + Ak x + O( x 2k )
n≤ x kπ
.
where A0, A1, … Ak are constants, especially when k equals to 2, A0=1; d(n) denotes the
Dirichlet divisor function,εis any fixed positive number.
For the sequence {b(n)} , we can also get similar result.
Theorem 2. For any real number x>1, we have the asymptotic formula
1
1 6 1− +ε
∑ d (b(n)) = kk! ( 2 )k −1 A0 x ln k x + A1x ln k −1 x +  + Ak −1x ln x + Ak x + O( x 2k )
n≤ x kπ
.
2. A SIMPLE LEMMA
To complete the proof of the theorems, we need following
Lemma 1. For any real number x>1, we have the asymptotic formula

1
1
1 6 k −1 +ε
∑ d (n k ) =
n≤ x
( 2 ) B0 x ln k x + B1 x ln k −1 x +  + Bk −1 x ln x + Bk x + O( x 2 ) .
k! π

where B0, B1,… Bk are constants, especially when k=2, A0=1;εis any fixed positive number.

d (n k )
Proof. Let s = σ + it be a complex number and f ( s ) = ∑ .
n =1 ns

ε
Note that d (n ) << n , So it is clear that f(s) is a Dirichlet series absolutely convergent in
k

Re(s)>1, by the Euler Product formula [2] and the definition of d(n) we have
 d ( pk ) d ( p2k ) d ( p kn ) 
f ( s ) = ∏ 1 + p s + p 2 s + + p ns + 
p  

 k + 1 2k + 1 kn + 1 
= ∏ 1 + s + 2 s +  + ns + 
p  p p p 

 1 
=ζ 2 ( s )∏ 
1 +( k −1) p s 

p  

 1 1 1 
= ζ 2 ( s )∏  (1 + s ) k −1 − C k2−1 2 s −  − ( k −1) s 
p  p p p 

ζ k +1 ( s )
= g ( s) . (1)
ζ k −1 ( 2s )

where ζ (s ) is Riemann zeta-function and ∏ p


denotes the product over all primes.

From (1) and Perron’s formula [3] we have


1 2+iT ζ k +1 ( s ) xs  x 2 +ε 
∑ d (n k ) = 2πi ∫2−iT ζ k −1 (2 s)
g ( s )
s
ds + O   , (2)
n≤ x  T 
1
where g (s ) is absolutely convergent in Re(s ) > + ε . We move the integration in (2) to
2
1
Re(s ) = + ε . The pole at s = 1 contributes to
2
1 6 k −1
( 2 ) B0 x ln k x + B1 x ln k −1 x +  + Bk −1 x ln x + Bk x , (3)
k! π

where B0 , B1 ,… Bk are constants, especially when k = 2, B0 = 1 .


1 1−σ
For ≤ σ < 1 , note that ζ ( s) = ζ (σ + it ) ≤ t 2 +ε . Thus, the horizontal integral contributes to
2
 1 +ε x 2 
O x 2 +  , (4)
 T 

2
and the vertical integral contributes to
 1 +ε 
O x 2 ln 4 T  . (5)
 
1 3
On the line Re(s ) = + ε , taking parameter T = x 2 , then combining (2), (3), (4) and (5) we have
2
k −1
1 6   12 + ε 
∑ d (n ) =  2 
k

k!  π 
B0 x ln x + B1 x ln
k k −1
x +  + Bk x + O x .
n≤ x  
This proves Lemma 1.

3. PROOFS OF THE THEOREMS


Now we complete the proof of the Theorems. First we prove Theorem 1.
For any real number x > 1 , Let M be a fixed positive integer such that

M k ≤ x < ( M + 1) k , (6)

then, from the definition of a(n), we have

M
∑ d (a(n)) = ∑ ∑ d (a(n) + ∑ d (a(n))
n≤ x m = 2 ( m −1) k ≤ n < m k M k ≤ n≤ x

M −1
= ∑ ∑ d (m k ) + ∑ d ( M k )
m =1 m k ≤ n < ( m +1) k M k ≤ n≤ x

M −1  
= ∑ (Ck1 mk −1 + Ck2 m k − 2 +  + 1)d (m k ) + O ∑ d ( M k )  ,
m =1  M k ≤ n ≤ ( M +1) k 
M
= k ∑ m k −1d (m k ) + O( M k −1+ ε) , (7)
m =1

ε
where we have used the estimate d (n) << n .

B( y) = ∑ d (n k )
Let n≤ y
, then by Abel’s identity and Lemma 1, we have

∑m
M
d (m k ) = M k −1B ( M ) − (k − 1) ∫ y k − 2 B( y )dy + O(1)
k −1
1
m =1

k −1  1 6 k −1 k −1 
 ( 2 ) B0 M ln M + B1M ln M +  + Bk M 
k
=M
 k! π 

M 1 6 
− (k − 1) ∫  ( 2 ) k −1 B0 y k −1 ln k y + B1 y k −1 ln k −1 y +  + Bk y k −1 dy
1
 k! π 

3
 k − 12 + ε 
+O  M 

 
k −1
1  6   k − 12 + ε 
=   B0 M ln M + C1M ln
k k k k −1
M +  + Ck −1M + O M
k
.
 (8)
kk!  π 2   
Applying (7) and (8) we obtain the asymptotic formula
k −1
1 6   k − 1 +ε 
∑ d (a(n)) =  
k! π 2 
B0 M k ln k M + C1M k ln k −1 M +  + Ck −1M k + O M 2  , (9)
n≤ x  

where B0 , C1 ,, Ck −1 are constants.

From (6) we have the estimates


0 ≤ x − M k < ( M + 1) k − M k = kM k −1 + Ck2 M k − 2 +  + 1

k −1
1 1
= M k −1 (k + Ck2 +  + k −1 ) << x k
, (10)
M M
and

 k −1  1
ln x
ln k x = k k ln k M + O 1  = k k ln k M + O( x k ) .
− +ε
(11)
 k 
 x 

Combining (9), (10) and (11) we have


1
1 6 1− + ε
∑ d (a(n)) = kk! ( 2 ) k −1 A0 x ln k x + A1x ln k −1 x +  + Ak −1x ln x + Ak x + O( x 2k ) ,
n≤ x kπ
where A0 equals to B0 .
This proves Theorem 1.
Using the methods of proving Theorem 1 we can also prove Theorem 2. This completes the proof of
the Theorems.

Acknowledgments
The author expresses his gratitude to professor Zhang Wenpeng for his very helps and detailed
instructions.

REFERENCES:
1. F.Smarandache, Only problems, not Solutions, Xiquan Publ. House, Chicago, 1993, PP. 35.
2. T.M.Apostol, Introduction to Analytic Number Theory, Springer-Verlag, New York, 1976.
3. Pan Chengdong and Pan Chengbiao, Foundation of Analytic Number Theory, Science Press, Beijing, 1997, PP. 98.
4. Zhang Wenpeng, On the cube part sequence of a positive integer (to appear).